Why Women Cannot Be Buddha? - Makcharoen, Pairor; Iso, Klairung (Journal of International Buddhist Studies, 2018)
Individuals who perform meritorious acts in order to be enlightened as Buddha in the future will need an important Dhamma qualification that is Dhammasamothan. This principle consists of eight associated qualifications: one of those is masculinity. In other words, it is suggested that only a gentleman can be enlightened like Buddha. Regarding on the fact that there is no clear reason the inferiors as stated in the Buddhist scripture; in addition, there are few researchers studying and mentioning the women’s inferiors for becoming Buddha. Therefore, this research aims at answering the questions that why this masculine qualification is required and why women cannot be enlightened as Buddha. According to the findings, the reasons why only men can be enlightened as Buddha are as follows: 1) the duties and missions of Buddha, 2) the natures and pains of women, 3) social, traditional and cultural conditions, and 4) the supports for Buddhist monks and householders who are men. The reason that women cannot be enlightened as Buddha is not because of the higher virtue of men. Women and men have equivalent potentials to perform meritorious acts and to have intentions, but appropriate contexts and environments are necessary for realizing the intentions. Hence, the enlightened ones must be men.